Management impacts on fire occurrence: A comparison of fire regimes of African and South American tropical savannas in different protected areas - Alvarado, Swanni T. [UNESP]; Silva, Thiago Sanna Freire [UNESP]; Archibald, Sally (Elsevier, 2018)
Humans can alter fire dynamics in grassland systems by changing fire frequency, fire seasonality and fuel conditions. These changes have effects on vegetation structure and recovery, species composition, and ecosystem function. Understanding how human management can affect fire regimes is vital to detect potential changes in the resilience of plant communities, and to predict vegetation responses to human interventions. We evaluated the fire regimes of two recently protected areas in Madagascar (Ibity and Itremo NPA) and one in Brazil (Serra do Cipó NP) before and after livestock exclusion and fire suppression policies. We compare the pre- and post-management fire history in these areas and analyze differences in terms of total annual burned area, density of ignitions, burn scar size distribution, fire return period and seasonal fire distribution. More than 90% of total park areas were burned at least once during the studied period, for all parks. We observed a significant reduction in the number of ignitions for Ibity NPA and Serra do Cipó NP after livestock exclusion and active fire suppression, but no significant change in total burned area for each protected area. We also observed a seasonal shift in burning, with fires happening later in the fire season (October–November) after management intervention. However, the protected areas in Madagascar had shorter fire return intervals (3.23 and 1.82 years) than those in Brazil (7.91 years). Our results demonstrate that fire exclusion is unattainable, and probably unwarranted in tropical grassland conservation areas, but show how human intervention in fire and vegetation patterns can alter various aspects of the fire regimes. This information can help with formulating realistic and effective fire management policies in these valuable conservation areas.
Keywords: Burn scar size distribution; Burned area; Fire regime; Fire return period; Management intervention; Number of ignitions; Seasonal fire distribution